Physicochemical characterisation and radical-scavenging activity of Cucurbitaceae seed oils - Jorge, Neuza [UNESP]; Silva, Ana Carolina da [UNESP]; Mayer, Cassia Roberta Malacrida [UNESP] (Taylor & Francis, 2015)
Oils extracted from Cucurbitaceae seeds were characterised for their fatty acid and tocopherol compositions. In addition, some physicochemical characteristics, total phenolic contents and the radical-scavenging activities were determined. Oil content amounted to 23.9% and 27.1% in melon and watermelon seeds, respectively. Physicochemical characteristics were similar to those of other edible oils and the oils showed significant antioxidant activities. Fatty acid composition showed total unsaturated fatty acid content of 85.2–83.5%, with linoleic acid being the dominant fatty acid (62.4–72.5%), followed by oleic acid (10.8–22.7%) and palmitic acid (9.2–9.8%). The oils, especially watermelon seed oil, showed high total tocopherol and phenolic contents. The γ-tocopherol was the predominant tocopherol in both oils representing 90.9 and 95.6% of the total tocopherols in melon and watermelon seed oils, respectively. The potential utilisation of melon and watermelon seed oils as a raw material for food, chemical and pharmaceutical industries appears to be favourable.
Keywords: Seed oil; Fatty acid composition; Tocopherol; Phenolic compounds; Antioxidants